Mathematical Modelling of Bödewadt Flow in Nanofluid: Implications of Velocity Slip and Thermal Slip Over a Stretching Disk - Lok, Yian Yian; Lim, Ming Hui (Journal of Science and Technology, 2024)
This paper investigates the flow and heat transfer attributes of Bödewadt flow in nanofluid, accounting for velocity slip, thermal slip, and a radially stretching permeable disk. The von Kármán similarity variables have been applied to simplify the governing partial differential equations into nonlinear ordinary differential equations, which are subsequently solved numerically using Python’s solve_bvp module. The results indicate that an adequate amount of stretching rate is required for the heat transfer equation's similarity solution to be present in the case of a no-slip stretching disk in order to satisfy the boundary conditions. The momentum and thermal boundary layer thickness are affected by the presence of velocity slip and thermal slip, along with stretching parameter. Additionally, variation of the local skin friction coefficient and local Nusselt number shows that heat transfer enhancement occurs in optimal situations when the slip value is minimal, a higher volume fraction of nanoparticles is used, and larger stretching parameters are applied.